DECODING DROUGHT RESILIENCE IN CHINESE ANNUAL RYEGRASS (Lolium multiflorum Lam.): INTEGRATED PHYSIO-BIOCHEMICAL PROFILING REVEALS BOLT AS A SUPERIOR DROUGHT-TOLERANT CULTIVAR - Xin Du; Ping Deng; Yang Luo; Tajie Sangzhu; Manjun Yang (Journal of Animal and Plant Sciences, 2025)
Annual ryegrass (Lolium multiflorum Lam.) cultivars, including Angus No.1, Abundant, Bolt, Jumbo, Tetragold, Barwoltra, and Diamond T, are widely cultivated in China for forage production. However, drought stress severely limits their yield and quality. This study investigated the drought tolerance mechanisms of these cultivars under 14-day extreme drought conditions. Physio-biochemical parameters, including chlorophyll content, osmoprotectants (saccharides, free amino acids, ascorbic acid), antioxidants (glutathione, polyphenols), oxidative damage markers (malondialdehyde (MDA), reactive oxygen species (ROS), superoxide anion), and structural components (cellulose, hemicellulose, lignin), were analyzed. This research found that Bolt exhibited superior drought tolerance, maintaining higher chlorophyll A (1.93 ± 0.035 mg/g), total chlorophyll (3.17 ± 0.065 mg/g), ascorbic acid (1885.9 ± 117.8μMol/g), and glutathione (234.2 ± 25.69 μg/g) compared to other cultivars. Additionally, Bolt showed enhanced hemicellulose accumulation (241.3 ± 3.21 mg/g) and minimal reduction in cellulose. Despite elevated MDA (13.93 ± 1.1nMol/g) and ROS (119,000 ± 4,000 relative fluorescence units (RFU)/g), Bolt’s robust antioxidant system and structural adaptations likely mitigated oxidative damage. Re-watering experiments confirmed Bolt’s resilience, underscoring its suitability for cultivation in arid areas. These results provide critical insights into selecting drought-tolerant ryegrass varieties for sustainable forage production in China.
Keywords: Lolium multiflorum; Drought stress; Antioxidants; Osmoprotectants; Cell wall components